2015
DOI: 10.1109/tie.2014.2387340
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Energy Trading in Microgrids: A Game-Theoretic Model and Its Equilibrium Analysis

Abstract: This paper proposes a distributed mechanism for energy trading among microgrids in a competitive market. We consider multiple interconnected microgrids in a region where, at a given time, some microgrids have superfluous energy for sale, or to keep in storage facilities, whereas some other microgrids wish to buy additional energy to meet local demands and/or storage requirements. Under our approach, the sellers lead the competition by independently deciding the amount of energy for sale subject to a trade-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
221
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 350 publications
(223 citation statements)
references
References 48 publications
1
221
0
1
Order By: Relevance
“…In this sense, there is a broker between the suppliers and the consumers who aggregates demand from all consumers and makes demand requests to suppliers based on the consumers' decisions. It should be noted that the broker concept is widely used in electric power market models to manage energy distribution, as in [4,5]. Here, the total amount of requested demand required to support the whole population is denoted by d req .…”
Section: Competitive Electric Power Market Model With Heterogeneous Pmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, there is a broker between the suppliers and the consumers who aggregates demand from all consumers and makes demand requests to suppliers based on the consumers' decisions. It should be noted that the broker concept is widely used in electric power market models to manage energy distribution, as in [4,5]. Here, the total amount of requested demand required to support the whole population is denoted by d req .…”
Section: Competitive Electric Power Market Model With Heterogeneous Pmentioning
confidence: 99%
“…The logarithm term is the consumers' gain from satisfaction in using a certain amount of electricity. Note that a logarithmic utility function is generally utilized to measure user's satisfaction with diminishing returns [4][5][6]. In this study, the total requested demand for electricity is defined as a constant.…”
Section: The Net Utility Function Of Consumers (Social Welfare)mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that such direct trading of electricity could be beneficial for both sellers and buyers, as the price of the electricity traded directly lies between the wholesale and retail price. Lee et al [7] proposed a distributed model for electricity trading among microgrids in a competitive market. Under their approach, sellers lead the competition by independently deciding the amount of electricity for sale, whereas buyers follow the sellers' actions by independently submitting a unit price bid to the sellers.…”
Section: B Electricity Markets Proposed In the Literaturementioning
confidence: 99%
“…Several papers [5]- [7] have proposed market models which allow users to negotiate a price and sell their excess electricity to different suppliers. These models are good for RES owners as the users can potentially increase their revenues by selling electricity at a higher price.…”
Section: Introductionmentioning
confidence: 99%